2002
DOI: 10.1111/j.1651-2227.2002.tb02875.x
|View full text |Cite
|
Sign up to set email alerts
|

Fasting levels of serum glucose, cholesterol and triglyceride at age eleven to twelve years in stunted and non‐stunted Jamaican children

Abstract: Aim: To determine whether fasting serum concentrations of glucose, cholesterol and triglyceride at age 11–12 y (a) differed between children stunted in early childhood and those who were never stunted, (b) were related to birthweight or current anthropometry and (c) were related to stunting after controlling for current size. Methods: Anthropometry, serum glucose and lipid concentrations were measured in 112 children stunted in early childhood and 181 non‐stunted children. Results: Children who were stunted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
2
3
1
Order By: Relevance
“…Greater increases in weight for height or subscapular skinfold are associated with higher outcome TC among 0-5 year old boys and all three cohorts of girls, with greater increases in TC among 6-11 and 12-19 year old girls, and with higher triglycerides among 6-11 and 12-19 year old boys and 12-19 year old girls. Our results are generally in accord with those studies that report weight gain in infancy or childhood is associated with higher outcome triglycerides (Donker et al, 1997;Bavdekar et al, 1999;Bennett et al, 2002;Dwyer et al, 2002;Parker et al, 2003;Fagerberg et al, 2004;Kajantie et al, 2008;Sayers et al, 2009) and higher outcome TC (Bavdekar et al, 1999;Bennett et al, 2002;Dwyer et al, 2002;Kuzawa and Adair 2003;Owen et al, 2003;Skidmore et al, 2007;Horta et al, 2009;Tzoulaki et al, 2010). Once again, however, not all studies follow this pattern.…”
Section: Childhood Fat and Adult Lipidssupporting
confidence: 92%
See 3 more Smart Citations
“…Greater increases in weight for height or subscapular skinfold are associated with higher outcome TC among 0-5 year old boys and all three cohorts of girls, with greater increases in TC among 6-11 and 12-19 year old girls, and with higher triglycerides among 6-11 and 12-19 year old boys and 12-19 year old girls. Our results are generally in accord with those studies that report weight gain in infancy or childhood is associated with higher outcome triglycerides (Donker et al, 1997;Bavdekar et al, 1999;Bennett et al, 2002;Dwyer et al, 2002;Parker et al, 2003;Fagerberg et al, 2004;Kajantie et al, 2008;Sayers et al, 2009) and higher outcome TC (Bavdekar et al, 1999;Bennett et al, 2002;Dwyer et al, 2002;Kuzawa and Adair 2003;Owen et al, 2003;Skidmore et al, 2007;Horta et al, 2009;Tzoulaki et al, 2010). Once again, however, not all studies follow this pattern.…”
Section: Childhood Fat and Adult Lipidssupporting
confidence: 92%
“…This is not atypical as other studies also have reported contradictory associations. While some have shown a negative correlation between stature growth and outcome TC, similar to our results (Cianfarani et al, 2003;Skidmore et al, 2007;Kajantie et al, 2008), others have reported a positive association (Tenhola et al, 2000;Miura et al, 2001), and still others could find no significant association (Bennett et al, 2002). While we found no significant relation between initial stature and outcome TC among the youngest children, others have found that shorter height among children between 4 and 11 years was associated with higher TC at age 20 (Skidmore et al, 2004), that stature at 8 years was positively related to TC (Bavdekar et al, 1999), or that stature at age 20 was positively associated with TC (Miura et al, 2001), as in our study.…”
Section: Childhood Stature and Adult Lipidssupporting
confidence: 87%
See 2 more Smart Citations
“…In summary, a modern lifestyle with excessive energy intake and insufficient physical activity causes weight increase and obesity, which may influence insulin sensitivity in preschool children. Nonetheless, we do not see any effect on fasting plasma glucose levels, which have remained constant in healthy children for more than 25 years (16–21).…”
Section: Discussioncontrasting
confidence: 66%